PEMANFAATAN DAUN SEBAGAI BAHAN PEMBUNGKUS MAKANAN DI KABUPATEN BANGKA TENGAH - Yulia Sari; Budi Afriyansyah; Lina Juairiah (EKOTONIA: Jurnal Penelitian Biologi, Botani, Zoologi, dan Mikrobiologi, 2019)
Traditional food is a food and drink that is usually consumed by certain people, with a distinctive taste that is accepted by the community. This study aims to record, reveal, document community knowledge about plant species and how to use them as food packaging material by the people of Central Bangka Regency and to find out the conservation status or level of threat of species. The research method was conducted by interviewing the criteria of key informants, field observations, anatomical observations and cluster analysis with pastpogram software and in determining the location using purposive sampling. The results of the study obtained 10 types of plants whose leaves are used as food and food wrappers consisting of 7 families. The most widely used families are Arecaceae, Pandanaceae and Poaceae. The highest number of plant species based on habitat is 9(43%). The highest number of plant species based on habitus is herbs 5(50%). Based on the results of the cluster analysis, most people use banana leaves (Musa sp.) as food and food packaging.